The influence of social support on work engagement and turnover intention: A study among Malaysian women working in the UK. - Tee, Hong Mei (2017)
Despite a large amount of research on social support among Western societies, there is limited research on non-Western women’s experiences of social support as well as the influence of social support on work performance. Hence, drawing from Job Demands-Resources (JD-R) model, this study explores the impact of social support on work engagement and turnover intention. A semi-structured interview was carried out with 7 Malaysian women working in the UK. The findings showed that all participants had a supportive work environment in their workplace such as the guidance, suggestions and supports from supervisors and colleagues. Concerning the effectiveness of social support, the findings confirmed the Job Demands-Resources (JD-R) model and showed that the existence of social support led to a better work performance. For instance, the availability of social support increased the satisfaction and engagement level towards their job, thereby lowering the intention to leave the job, suggesting that social support had a positive relationship with work engagement and a negative relationship with turnover intention. The limitations and reflexivity are provided. The implications and recommendations for future studies are also discussed.